2015
DOI: 10.3390/f6113809
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Annual Xylem Growth of Larix principis-rupprechtii at Its Upper and Lower Distribution Limits on the Luyashan Mountain in North-Central China

Abstract: Altitude-related climatic factors, especially temperature, are important factors that affect tree growth in mountain forest ecosystems. The aims of this study were to estimate the intra-annual radial growth differences of Larix principis-rupprechtii (L. principis-rupprechtii) between its upper and lower distribution limits, at 2740 and 2040 m a.s.l, respectively. Dynamics of xylem growth were observed by collecting microcore samples weekly during the 2011 growth season. The result indicated that different stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…The wet-season moisture constraint on tree-ring width of Taiwan pine and Bashan fir (Abies fargesii) in subtropical China was also demonstrated by dendrochronological studies, where warming-induced drought was detected in the early growing season [6,39]. Nevertheless, our results contrast with the non-elevation effects on growth-climate relationships in semi-arid [27,29] and cold-limited forests [35]. Physiologically, xylem cell enlargement and stem radial growth is a turgor-driven process, which requires a continuous maintenance of stem water saturation [30,31].…”
Section: Seasonal Drought Effects On Stem Radial Growthsupporting
confidence: 69%
See 1 more Smart Citation
“…The wet-season moisture constraint on tree-ring width of Taiwan pine and Bashan fir (Abies fargesii) in subtropical China was also demonstrated by dendrochronological studies, where warming-induced drought was detected in the early growing season [6,39]. Nevertheless, our results contrast with the non-elevation effects on growth-climate relationships in semi-arid [27,29] and cold-limited forests [35]. Physiologically, xylem cell enlargement and stem radial growth is a turgor-driven process, which requires a continuous maintenance of stem water saturation [30,31].…”
Section: Seasonal Drought Effects On Stem Radial Growthsupporting
confidence: 69%
“…The synchronized starting of stem growth across elevations is consistent with the elevational transect investigations in semi-arid mountains [25,29], but contrasts with results from cold-limited forests [24,[26][27][28]35]. Temperature has been long recognized as the major trigger of the growth initiation of coniferous and broadleaf trees across temperate and boreal forests [17,24,27,28], and most studies have repeatedly reported that a physiological threshold daily minimum temperature of ≥ 4-5 • C is related to cambial reactivation and xylem cell differentiation [17].…”
Section: Intra-annual Stem Growth Dynamics Along the Elevation Transectsupporting
confidence: 63%
“…The rapid stem radius growth in this study was observed in the time from May to July (stage 1), coincident with the most rapid division rate of cambial cells [37]. The rapid growth stage is considered as a critical stage for the formation of early wood cell and stem radius growth.…”
Section: Intra-annual Variations Of Stem Radiusmentioning
confidence: 58%
“…In our study, soil temperature was important for both primary growth and secondary growth (Table 4). Previous research in this study area has shown that soil temperature played a key role for the initiation of radial growth for both larch and spruce [8,44]. The threshold value of soil temperature for larch xylogenesis was above 0 • C as frozen soil will inhibit water uptake and activity in root systems [45].…”
Section: Environmental Effect On Growthmentioning
confidence: 88%
“…Studies on secondary growth have revealed an early onset of cambium activity, as well as a longer duration of xylem formation, and this has often been related to the influences of ongoing climate change [5,6]. Therefore, investigations on primary and secondary growth help to assess the physiological adaptation of species to the local environment [7] and predict changes in the growing season under current global warming [8].…”
Section: Introductionmentioning
confidence: 99%